(untitled) (Scientific journal of the Fergana State University, 2025)
Different mineral and organic fertilizers are used in the required amount so that the microelements in the soil can be well absorbed by the plant. In order to increase cotton productivity, one of the urgent issues is to study and determine the terms and norms of using not only mineral fertilizers and liquid NPK fertilizers, but also the use of physiologically active substances that are newly produced today is considered.